The impact of investors' behavior and managers' overconfidence on stock return: Evidence from Iran - Hossein Jokar; Vahid Daneshi (Cogent Business & Management, 2018)
The purpose of the present study is to investigate the effect of behavioral variables on overconfidence in management, herding behavior and investors' emotional tendency on stock return. To this end, by using the data of firms listed in Iran's Stock Exchange during the seven-year period of 2010–2016, overconfidence index in management, the herding behavior of the investors and the emotional tendency of the investors were calculated and their impact on stock return was examined. The data of the research are of a panel type and for analyzing the data and testing the hypotheses; a multiple linear regression model has been used. Evidence from the experimental results of the research showed that the behavioral variables studied in the research has a significant and inverse effect on the stock return of the companies.
Keywords: 650